2013
DOI: 10.1111/his.12202
|View full text |Cite
|
Sign up to set email alerts
|

Expression of moesin and CD44 is associated with poor prognosis in gastric adenocarcinoma

Abstract: Moesin expression and CD44 expression might be useful markers of poor prognosis in gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
0
27
1
4
Order By: Relevance
“…This finding is contrary to that of Jung et al who demonstrated significant differences only in highly expressing CD44 patients and overall survival using KaplanMeier curves and independently of pathological TNM stage and histological grade (28).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is contrary to that of Jung et al who demonstrated significant differences only in highly expressing CD44 patients and overall survival using KaplanMeier curves and independently of pathological TNM stage and histological grade (28).…”
Section: Discussioncontrasting
confidence: 99%
“…Interaction between moesin and CD44 is known to be an important process in the EMT of tumor cells (20,27). Nevertheless, Jung et al demonstrated that the expression of CD44 was an independent indicator of poor prognosis but was not correlated with other clinicopathological factors, nor with moesin expression (28).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, CD44 may also symbolize a potential marker of OSCC stem cells. 17,18 This study confirms the expression of stem cell surface marker CD44 expression in OSCC tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype has been observed in CSC derived from prostate, breast, pancreatic, and gastric tumors [17]. Interestingly, CD44 overexpression has been associated with poor prognosis and reduced overall survival in GC [107]. CD44 is a cell surface receptor, which mediates interaction with ECM component, particularly HA [107].…”
Section: Molecular Signatures Independent Of Histologic Subtypementioning
confidence: 91%